Blood Ties : How a Texas Prison Gang Became a Mexican Cartel Proxy - Kolb, Joseph (Book collections on Project MUSE., 2021)
"In the late 1980s and 1990s, street gang members from the impoverished Segundo Barrio in El Paso, Texas, united in the Texas prison system to create the Barrio Aztecas gang. They quickly rose to power in the Texas prison system and ultimately became a powerful transnational criminal organization. Kolb describes the prison dynamic of predator and prey and the need for the prey to unify for protection against gangs such as the Texas Syndicate and Texas Mexican Mafia, also known as the Mexikanemi. The protective cocoon formed by this group soon morphed into a criminal enterprise that would be headquartered in the Coffield Unit of the Texas Department of Criminal Justice, where the gang would engage in drug sales and violent crimes while behind bars. The skill sets they acquired served members well as they were released from custody and went on to exploit US immigration policies as well as friends and familial ties in Ciudad Juárez, Mexico. There they established alliances with regional drug trafficking organizations such as Vicente Carrillo Fuentes (Juarez cartel), to whom they would serve as foot soldiers in the proxy war that would consume Ciudad Juárez and turn it into the "Murder Capital of the World." Blood Ties describes the Azteca's organizational structure and ranks, identifying characteristics such as tattoos and code words, and how the organization appropriated Aztec culture to form the basis for their identity. Some of the gang's most horrific crimes are revealed here, and the author explores how Azteca's leadership was eroded through the violation of the very tenets that served as the gang's foundation"--